Studying policy diffusion at the individual level: Experiments on nationalistic biases in information seeking - de Vries, Catherine; Butler, Daniel M.; Solaz, Hector (Sage Journals, 2019)
The foundational assumptions of policy diffusion relate to the behavior of individual policymakers. However, empirical tests of policy diffusion often focus on the behavior of governments as a whole (and not individuals). We provide a template for how to study the behavioral decisions of policymakers related to policy diffusion. Our particular field experiments test whether there is a bias toward seeking out information on the policy experiences of local governments in one’s own country as opposed to governments outside of the country. The experimental evidence shows that local officials do not exhibit this bias. Further, they do not exhibit a bias against information about policies that have received an EU endorsement. Our results are a positive sign that nationalistic forces are not diminishing inter-country, policy diffusion within Europe, and our design provides a template for future experiments on policy diffusion.
Keywords: Policy diffusion; experiment; Europe; 59 Ciencia Política; ODS 10 - Reducción de las desigualdades